An assessment of the quality of GPS water vapour estimates and their use in operational meteorology and climate monitoring - Jones, Jonathan (2010)
The path delay between a GPS satellite and a ground based GPS receiver depends, after elimination of ionospheric effects using a combination of the two GPS frequencies, on the integral effect of the densities of dry air and water vapour along the signal path. The total delay in the signal from each satellite is known as the slant delay as the path is most likely to be non-azimuthal. The slant paths are then transferred into the vertical (or zenith) by an elevation mapping function, and this new parameter is known as the Zenith Total Delay or ZTD. ZTD gives a measure for the integrated tropospheric condition and is now widely accepted as a standard product from a network of dual frequency GPS receivers. With further calculation, taking into account surface pressure and temperature, we can then convert a portion of the ZTD into an estimate of the Integrated Water Vapour content of the atmosphere (IWV).